Experimental Study of Abrasive Waterjet Cutting for Managing Residues in No-Tillage Techniques - Francesco Perotti; Massimiliano Annoni; Aldo Calcante; Michele Monno; Valerio Mussi; Roberto Oberti (Agriculture, 2021)
A laboratory investigation of abrasive waterjet cutting of wheat straws was conducted. The work was aimed at a systematic characterization of the abrasive waterjet cutting capability of wheat straws, as a potential alternative to cutting discs currently adopted in no-till drills and planters for crop residue management. A two level <semantics><msubsup>2IV7−3</msubsup></semantics> fractional factorial design was applied to investigate the influence of abrasive waterjet process parameters on the cutting efficiency of wheat straws. Straw coverage thickness, water pressure, and orifice diameter were found to be the most significant ones. Experimental results suggest that straw cutting mechanism is mostly related to the hydraulic power of the jet. A multiple logistic regression was performed to model the relationship between the cutting efficiency and the jet power. The logistic model was then applied to estimate the average water and power consumption for wheat straw cutting during a no-tillage seeding operation. An average jet hydraulic power of 6400 W would be sufficiently high to guarantee 90% cutting efficiency in presence of heavy residue distribution. The experimental study shows that a small quantity of abrasive powder (50 g·min−1) allows one to increase the jet cutting capability of wheat straws, and to reduce the required maximum hydraulic power, compared to pure waterjet cutting. Results show are potentially relevant for field validation in agriculture based on no-tillage.